Scratch Holograms Drawn by Computer Using a Laser Engraver System - Augier, Ángel G.; Sánchez, Raúl. B. (Revista Cubana de Física; Vol 27 No 1 (2010), 2010)
A computing generalization of the non-conventional holographic technique, well-known as Scratch Holography or Hand Drawn Holography, is developed. It is presented an alternative technique that allows to code threedimensional virtual objects (3D) as two-dimensional (2D) multiple circular-scratch drawings, using a software program for 2D encoded representation of 3D-models. Using this software like an assistant, several scratch holograms of variable complexity were hand drawn, generated by software templates. A CO2 laser engraver system, driven by computer, was used for drawing more complex holograms directly onto suitable surface. Different types of plastic material are employed. Reconstructed images from all these holograms are shown.